Front Cover: 2′/3′ Regioselectivity of Enzyme‐Free Copying of RNA Detected by NMR (ChemBioChem 14/2020). (8th July 2020) - Motsch, Sebastian; Pfeffer, Daniel; Richert, Clemens
Abstract : Caught by spectroscopy : Enzyme‐free copying of RNA is a reaction that produces more than one regioisomer of the phosphodiester linkage between the growing strand and the incoming nucleotide. Enzymatic read‐out of the regioselectivity can be biased by substrate specificity and destroys the RNA. Using NMR as non‐invasive, spectroscopic technique, the effect of nucleotide activation and neighboring strands was measured in hairpin systems. More information can be found in the full paper by C. Richert et al.